PL/ODQL object enhancement of ODQL query language for Dynamic information model DIM - D. S. Pisarenko (Моделирование и анализ информационных систем)
Considered a task of creating a computing complete enhancement for ODQL [1] object-dynamic query language. The enhancement should be convenient in DIM system objects manipulating. The enhancement syntax description is stated.